STRATEGI PENGEMBANGAN MAHARAH AL-KALAM SISWA DALAM MATA PELAJARAN MUHADATSAH DI MADRASAH ALIYAH ALKHAIRAAT KOTA GORONTALO - Paputungan, Moh. Zulkifli (IAIN Batusangkar, Indonesia, 2020)
The purpose of this research is to describe (1) the development strategies of maharah al-kalam (studentsâ€™ speaking skill) in Muhadatsah course at Madrasah Aliyah Alkhairaat Kota Gorontalo, (2) problems in the development strategy of maharah al-kalam (studentsâ€™speaking skill) in Muhadatsah course, (3) the solutions to overcome problems in the strategy of developing maharah al-kalam (studentsâ€™speaking skill) in Muhadatsah. This is a descriptive qualitative research using an educative approach. The data collection method were observation and interview. Strategy in developing maharah al-kalam (studentsâ€™ speaking skill) in Madrasah Aliyah Alkhairaat, Gorontalo included eight strategies and exercises. The data sources were from the teacher, students, the principal and the leader of Islamic Boarding School. But, just a few students are able to speak arabic language and mastering Ù…Ù‡Ø§Ø±Ø©Ø§Ù„ÙƒÙ„Ø§Ù… (speaking skill) after they have class of Ø§Ù„Ù…ØØ§Ø¯Ø«Ø© (conversation). Some problems are found variously, such as: (1) less of teacher of Ø§Ù„Ù…ØØ§Ø¯Ø«Ø© (conversation) and it can be solved by adding some more professional teachers. (2) less of using arabic language in the teachersâ€™ daily life that can be solved by making some written rules and instruction for all of the teachers and staff to speak arabic language in the school. (3) Obligating the students to speak arabic language wherever they are and give punishment to whom did not do it. (4) Realizing the program â€œPemberantasan Buta Bahasa Arabâ€ and provide dormitory for the students who live outside the school. And (5) making an innovative way about language development program by involving the studentsâ€™ parents.